The availability, use and disposal of malaria and HIV rapid diagnostic test kits in health facilities in the greater Accra region of Ghana - Amartey, Akua O.; Buabeng, Kwame O.; Tengey, Senam; Maru, Shital M. (International Journal Of Community Medicine And Public Health, 2020)
Background: The Malaria and HIV rapid diagnostic tests (RDTs) are some of the commonest tests that are used in Ghana to support malaria and HIV management/care respectively. When these devices are used, they are categorized as potentially infectious. This paper aims to highlight the availability and management of used malaria and HIV RDTs in various healthcare facilities and by health service providers in the greater Accra region of Ghana. Methods: Data was obtained from 400 health facilities including hospitals, clinics, health centres, and pharmacies and over the counter medicine seller’s shops using purposive sampling technique with the aid of structured questionnaires and observation of practices. Results: Seventy percent of the facilities (n=280) used only malaria RDTs, 29% (n=116) used both malaria and HIV RDTs and 1% (n=4) reported using HIV RDTs only. 81.7% (n=326) which formed the majority used less than 10 RDTs daily. There was poor waste segregation, storage, transportation, treatment and disposal of waste. Facilities that had some sort of on-site treatment of waste used single chambered incinerators. Conclusions: Each of the categories of health facilities had a common practice of poor hazardous waste management. We therefore recommend that there should be enhancement of education and training of practitioners in the health facilities and the general public on the optimal use of the RDTs and disposal or the management of healthcare waste in general. The environmental protection agency and ministry of health should collaborate and enforce all the regulations on healthcare waste management in the various facilities.